L’indemnisation du stress au travail - Lippel, Katherine (Assurances, 1992)
The author discusses the recovery of payment for disability under workers' compensation legislation in Québec, English Canada and the United States, with a focus on Québec. Ms. Lippel looks at both physical and psychological disabilities attributable to psychological stress in the workplace. She shows that while many American states have been compensating for both types of disability for several years, Canadian tribunals are only starting to recognize such claims. Québec is at the forefront, in Canada, in recognizing psychological disability related to chronic workplace stress, but lags behind other provinces when it comes to heart attack claims. Recognition of claims related to chronic workplace stress is still difficult to obtain. Workers must demonstrate that they are physically or psychologically disabled, and that their disability is most probably attributable to workplace stressors.